The Students’ and Teachers’ Perception of the Use of Digital Storytelling within the Project-Based Learning Approach for Engaging Undergraduate Students in English - Mahril, Rijal (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2023)
One of the major issues in achieving a more effective learning process is the lack of productive instructional activities that require students’ engagement. Consequently, it is encouraged by academics to promote high levels of student engagement, especially in instructional design. This study investigates students’ and teachers’ perceptions of using Digital Storytelling (DST) within a Project-Based Learning (PBL) approach to encourage cognitive engagement in English language classrooms. DST employs the ADDIE Model as its conceptual framework. Data were collected using qualitative methods through online surveys and semi-structured interviews involving 10 English lecturers and 10 English Education students at Muhammadiyah University of Makassar in 2018. The findings indicate that DST positively impacts engagement by fostering creativity, enhancing motivation, and improving critical thinking skills. The integration of DST in language learning offers significant benefits, highlighting the need for innovation in educational practices.